Pengembangan Media Augmented Reality Berbantuan Assemblr Edu untuk Meningkatkan Motivasi dan Kemampuan Berpikir Kritis Siswa - Nita Yeni Asmara; Yanti Fitria; Muhammadi Muhammadi; Ulfia Rahmi (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to develop Augmented Reality learning media assisted by Assemblr Edu and to examine its validity, practicality, and effectiveness in improving the motivation and critical thinking skills of fifth-grade elementary school students in Natural Sciences (IPAS). The low level of students’ motivation and critical thinking skills is mainly caused by the limited use of innovative learning media. This research employs a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research instruments include validation sheets, teacher and student response questionnaires, and critical thinking tests. Data analysis techniques involve quantitative analysis using descriptive statistics in percentage form to determine the validity and practicality of the media, as well as the N-Gain test to measure the improvement in critical thinking skills, along with qualitative analysis from observations, interviews, and expert feedback. The results show that the developed media achieved a validity score of 96% (very valid), practicality scores of 96.6% from teachers and 96.30% from students (very practical), and an N-Gain score of 0.719 (high effectiveness). These findings indicate that the Augmented Reality media assisted by Assemblr Edu is feasible, practical, and effective in supporting interactive and meaningful learning in elementary schools